Ibuprofen with Acetaminophen for Postoperative Pain Control following Tonsillectomy Does Not Increase Emergency Department Utilization. (December 2014) - Bedwell, Joshua R.; Pierce, Matthew; Levy, Michelle; Shah, Rahul K.
Objective: To compare the performance of ibuprofen vs codeine for postoperative pain management after tonsillectomy as measured by need for emergency department (ED) treatment for pain and/or dehydration. Study Design: Retrospective case series with chart review. Setting: Tertiary children's hospital. Subjects and Methods: Consecutive series of patients who underwent tonsillectomy with or without adenoidectomy at a tertiary children's hospital. Patients were categorized based on the type of postoperative pain management (acetaminophen with codeine vs acetaminophen and ibuprofen). The main outcome measure was the proportion of patients requiring ED visits or inpatient admissions for inadequate pain control or dehydration. Secondary measures included antibiotic use, postoperative hemorrhage, need for return to the operating room, vomiting, and oral diet tolerance. Results: Patients in the ibuprofen/acetaminophen group were younger than those in the codeine/acetaminophen group (6.2 vs 8.1 years, P < .05). Patients in the codeine/acetaminophen group were more likely to use antibiotics in the postoperative period (50.3% vs 5.9%, P < .05). The proportion of patients requiring ED visits or inpatient admission for dehydration was not significantly different between the groups (5.1% for codeine, 2.7% for ibuprofen, P = .12). Multivariable analysis controlling for age and antibiotic use showed no difference in ED visits or admission for dehydration ( P = .09). There was no difference between the groups for any of the secondary measures. Conclusions: Ibuprofen with acetaminophen represents a safe and acceptable analgesic alternative to codeine and acetaminophen in patients undergoing pediatric tonsillectomy.